Teacher returnees from overseas programs in the west: a narrative study in Vietnam - Vu, Ngoc Tung; Ta, Thi Mai Huong; Le, Thi Thu Huong (Frontiers in Communication, 2024)
In this narrative inquiry research, our focus was on exploring teacher identity within the context of the expanding field of language teacher education and professional development. Utilizing theories of teacher identities to analyze data from interviews and reflections, we observed that conversations and stories were frequently shared in social settings, with overseas teaching practices being a substantial influence on their reflections. The findings indicated that the participants' teacher identities continually changed and dynamically evolved, particularly influenced by their engagement in overseas educational programs. Upon their return, participants expressed hope in maintaining their newly transformed perspectives on teaching and learning. In conclusion, we discussed further research directions and implications to underscore the ongoing significance of this topic.